Literacy, Compliance, and Digital Legal Awareness: The Role of JDIH UNNES in Disseminating Legal Information - Wulandari, Cahya; Sugianto, Sugianto; Putra, Anggyi Trisnawan; Emha, Zidney Ilma Fazaada; Hassan, Muhamad Sayuti (Indonesian Journal of Advocacy and Legal Services, 2025)
Public legal awareness is an important foundation in creating a fair and effective legal system. The low level of legal understanding is the main trigger for public non-compliance with the law. Therefore, legal literacy is a strategic key in shaping legal awareness. The novelty of this article discusses the urgency of legal literacy and compliance in realizing a law-aware society and highlights the role of JDIH UNNES as an important tool in disseminating legal information. The method used in this study is normative juridical. The results of this study show that legal literacy not only includes the ability to understand the content of the law, but also encourages proactive legal attitudes and behavior. JDIH UNNES has proven to play a strategic role in providing legal information that is easily accessible, accurate, and relevant so as to support information disclosure and public participation in law enforcement and encourage the development of a legal culture in Indonesia. Thus, strengthening legal literacy through means such as JDIH has practical implications in shaping a society that understands, obeys, and is aware of the law in a sustainable manner.